2022
DOI: 10.3389/fspor.2022.975900
|View full text |Cite
|
Sign up to set email alerts
|

Growth, maturation and injuries in high-level youth football (soccer): A mini review

Abstract: Understanding the challenges football (soccer) players face during adolescence is fundamental to avoid disruptions in their development due to injury. This mini review will describe basic concepts of somatic growth and biological maturity, examine data from 53 prospective epidemiological studies on high-level youth football players and discuss how age, growth and maturity may affect the injury patterns observed. Based on the existing evidence, at least every third player sustains an injury during a football se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 98 publications
2
11
0
Order By: Relevance
“…To the best of our knowledge, this study is the irst to reveal the developmental stage describing PHV age ± 6 months as a risk factor of OSD development prospectively. Consistent with our results, several studies have reported that the prevalence of sports injuries among adolescent soccer players is high during 6 months before or after the PHV age [6,27,46,49], and van der Sluis et al [45] demonstrated coaches and trainers should be careful with the training and match load on the soccer players at around the PHV age to minimize the risk of injuries. Around the PHV age, not only the attachments of muscle tendons are stressed by the muscle shortening [41,50], but the rapid growth of the limbs deteriorates balance and causes clumsy movements [21,34,35,37].…”
Section: Developmental Stagesupporting
confidence: 92%
“…To the best of our knowledge, this study is the irst to reveal the developmental stage describing PHV age ± 6 months as a risk factor of OSD development prospectively. Consistent with our results, several studies have reported that the prevalence of sports injuries among adolescent soccer players is high during 6 months before or after the PHV age [6,27,46,49], and van der Sluis et al [45] demonstrated coaches and trainers should be careful with the training and match load on the soccer players at around the PHV age to minimize the risk of injuries. Around the PHV age, not only the attachments of muscle tendons are stressed by the muscle shortening [41,50], but the rapid growth of the limbs deteriorates balance and causes clumsy movements [21,34,35,37].…”
Section: Developmental Stagesupporting
confidence: 92%
“…Regarding the injury rate, young players with late development report higher injury rates than players with early development [ 64 ]; for this reason, it is necessary to give special attention to this kind of player in the adjustment of competitions.. Thus, the proposed rule modification reduces the number of accelerations and decelerations in zone 3, which is related to a lower injury rate, as distance covered, accelerations, and changes in pace are considered some of the main injury mechanisms in young players [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 The results of several recent studies linking higher growth rates (e.g., changes in height, leg length or body mass index) and peak height velocity have been associated with increased injury risk in high-level youth football players. [22][23][24] Injury frequency and incidence of injury were more than two times greater for males than females, as has been reported elsewhere in the ED literature.2,11,12,20 In addition to differences in social-related participation patterns, possible explanations include hormonal differences, increased joint laxity in female athletes, anatomical differences, and differences in motor control.26 However, girls tend to have higher exposure-based injury rates than boys in gender-comparable high school sports.27 Also, girls may actually be at increased risk for anterior cruciate ligament injuries in the knee28 and sport-related concussions. 29 In our study, the higher rates of injury in males were most pronounced in the 15-19 age group.…”
Section: Who Is Affected?mentioning
confidence: 99%
“…43 The finding of increased risk and severity of SRI's during the timing of the adolescent growth spurt warrants maturity-specific prevention programs where coaches are encouraged to identify periods of rapid growth where resources allow and monitor training load of individual athletes to reduce injury risk.22-24,44 Observing, talking to, and educating players and parents may be equally effective. 22 The employment of bio-banding, a method by which players are grouped together based on their maturity and biological age rather than their birth year, also could potentially help reduce the risk of injury among youth athletes. 45,46 Finally, the trend of increased frequency of injury among females during the study period is a concern, especially in view of research showing increased risk of for anterior cruciate ligament injuries in the knee28 and sport-related concussions.29 Injury prevention strategies specifically targeting these injury types are needed to reduce the increasing number of injuries in girls' SR activities.42,47 Irrespective of the trend of sports injuries, however, an effort should be made to decrease injuries in all SR activities to promote safe play in children.20…”
Section: Practical Applicationsmentioning
confidence: 99%